DAMP-TLR-cytokine axis dictates the fate of tumor. (April 2018) - Patidar, Ashok; Selvaraj, Sathishkumar; Sarode, Aditya; Chauhan, Prashant; Chattopadhyay, Debprasad; Saha, Bhaskar
Highlights: Tumor cell derived DAMPs interact with TLRs to trigger local and central effects. The local effects include tumor cells organization and microenvironment alteration. The central effects via T cell activation and trafficking add to the local effects. DAMP-TLR signals reciprocally alter angiogenesis, metastasis and T cell trafficking. The DAMP-TLR signaling and its effector functions may be targets for cancer therapy. Abstract: Random mutations leading to loss of cell cycle control is not a rare occurrence in an organism but the mutated cells are recognized and eliminated preventing the development of a tumor. These potentially tumorigenic cells release damage-associated molecular patterns (DAMPs), which are recognized by toll-like receptors (TLRs) on macrophages and dendritic cells. The initial TLR-DAMP interactions lead to different responses such as altered antigen presentation and cytokine release that directly affect T cell activation and removal of the tumorigenic cells. The indirect effects of TLR-DAMP interaction include chemokine-directed altered T cell trafficking, angiogenesis for both T cell infiltration and tumor cell metastasis, and alteration of intra-tumoral milieu contributing to the development of tumor cells heterogeneity. Thus, the initial TLR-DAMP interaction has a set of local effects that modulate tumor cell growth and heterogeneity and a disseminating set of central effects that dynamically affect T cell trafficking and functions. Herein, we argue that the DAMP-TLR-cytokine axis in the tumor microenvironment serves as the mainstay that orchestrates and regulates the pro- and anti-tumor elements which dynamically interact between themselves eventuating in tumor regression or growth. The knowledge of this TLR-based immuno-surveillance framework is a key to developing a novel immunotherapy against cancer.